Elderly drivers with pedal errors during emergency braking do not lift their leg - Kazuki Fujita; Yasutaka Kobayashi; Koji Hayashi; Kaori Kawabata; Tomoki Ogawa; Hideaki Hori; Mamiko Sato; Masahito Hitosugi (Transportation Research Interdisciplinary Perspectives)
Pedal errors among elderly drivers may be more closely associated with a decline in motor control rather than cognitive function. However, the impact of motor control across all major joints in the lower limb, including the hip, knee, and ankle joints, has not been thoroughly investigated. This study aimed to clarify the characteristics of lower limb kinematics and electrophysiology during emergency braking in individuals who commit pedal errors. The subjects comprised 30 men and women aged 75 years and older. An experimental pedal was employed, and the muscle activity and kinematic data during successful emergency braking action were analyzed. The light from a light-emitting diode installed in the front was adopted as a trigger. Among the 30 participants, 10 committed errors by pressing both pedals simultaneously. The error group exhibited a significantly delayed onset of rectus femoris activity and higher tibialis anterior electromyogram amplitude compared with the nonerror group. The error group also displayed low ranges of motion and angular velocities in hip and knee flexions as well as hip adduction. However, the hip internal rotation range was large. Those who avoided pedal errors lifted their legs by flexing the hip and knee, whereas those who made errors exhibited a habitual movement pattern of internally rotating the hip while keeping their heel on the floor. These findings suggest that specific movement patterns and declines in lower limb motor control contribute to pedal errors.